Perilaku Campuran Semen dan Fly Ash sebagai Bahan Dasar Mortar Instant untuk Pemasangan Keramik Dinding - Munafri Alwys -; Sudaryono - - (Jurnal Ilmiah Poli Rekayasa, 2014)
Steam Electrics Power Sijantang Sawahlunto in West Sumatra, produce fly ash waste from coal burning which is very much every day (about 300 tons/day). Air pollution caused by fly-ash has been disturbing the community surrounding due to environmental pollution, the pollution has been carried away by water flown to the rice fields, causing the rice crops of community are damage. It is already a big problem, because the public has repeatedly protested to the PLN, even the local government had been repeatedly requested to the PLN, to resolved that the issue soon.  To solved that problem, PLN in cooperation with Padang State of Polytechnic, has done some research in order to utilize the waste fly ash into building materials. The results of this study prove that the waste fly ash can be used as the basic material to produce instant tiling mortar. Through research conducted, it is found a smart way out, where "there is a problem that can be used as an opportunity" especially if people are trained and given the opportunity to produce mortar instant in their homes (home industry), it will be able to improve the economy and welfare of the people around the plant Sijantang.